2021
DOI: 10.21203/rs.3.rs-163508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Historic Grazing Enhances Root-Foraging Plasticity and Assimilation But Not Absorbability For Nitrogen of Clonal Offspring in Leymus Chinensis

Abstract: Aims Plants with a history of overgrazing show trait-mediated legacy effects. These legacy effects strongly influence growth dynamics and stress tolerance of grassland plants, thus impacting ecosystem functioning. Long-term overgrazing has strong effects on plant growth and carbon assimilation via asexual propagation. However, the links between nitrogen (N) cycling and grazing-induced plant legacy effects are largely unknown.Methods We tested the strength of legacy effects of long-term overgrazing on N metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Previous research has suggested that L. chinensis exhibits strong plasticity in its reproductive characteristics, particularly in response to inter-annual variations in resource availability [ 59 ]. This plasticity enables clonal plants to regulate population stability and promote ecological balance through quantitative adjustments [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that L. chinensis exhibits strong plasticity in its reproductive characteristics, particularly in response to inter-annual variations in resource availability [ 59 ]. This plasticity enables clonal plants to regulate population stability and promote ecological balance through quantitative adjustments [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%